Parents’ perception of social skills in children with learning disabilities in Abuja, Nigeria - Olabisi, Akinola Patrick; Ahmad, Sa’odah; Daud, Mohd Najmi (Human Resources Management Academic Research Society (HRMARS), 2024)
The relationship between a child and his or her family environment is perhaps the greatest influence on a child's life. Developments of social skills started at home through interaction with parents. This study examined parents’ perceptions of social skills in children with learning disabilities in Abuja, Nigeria. The participants of this study were 314 female and male parents of children with learning disabilities selected from 20 inclusive basics schools across the six Area Councils of the Federal Capital Territory (FCT) Abuja. Parents' perceptions of the social skills in children with learning disabilities were measured using the Social Skills Questionnaire (SSQ-P, Spence, 1995). A t-test was used to determine the difference in female and male parents' perceptions of the social skills of children with learning disabilities. The result showed that female and male parents’ perception of the social skills in children with learning disabilities was moderate. There was no significant difference in the perception of social skills of children with learning disabilities based on the gender of the parents. Given that parents have rated the social skills of their children with learning disabilities as moderate, it is important for intervention programs and policies to prioritize supporting parents and schools in fostering appropriate social skills and preventing social skill deficits in children.